Sigmatropic rearrangements of cyclopropenylcarbinol derivatives. Access to diversely substituted alkylidenecyclopropanes - Ernouf, Guillaume; Brayer, Jean-Louis; Meyer, Christophe; Cossy, Janine (Beilstein Journal of Organic Chemistry, 2019)
Cyclopropenes constitute useful precursors of other classes of compounds incorporating a three-membered ring. Although the transformation of substituted cyclopropenes into alkylidenecyclopropanes can be accomplished through different strategies, this review is focusing specifically on the use of [2,3]- and [3,3]-sigmatropic rearrangements involving cyclopropenylcarbinol derivatives as substrates. These sigmatropic rearrangements, which have been developed in recent years, allow a remarkably efficient and stereoselective access to a wide variety of heterosubstituted and/or functionalized alkylidenecyclopropanes which would not be readily accessible by other strategies. The different [2,3]- and [3,3]-sigmatropic rearrangements of cyclopropenylcarbinol derivatives disclosed to date, as well as the analysis of their substrate scope and some applications of the products arising from those reactions, are presented in this review.
Keywords: alkylidenecyclopropanes; cyclopropanes; cyclopropenes; sigmatropic rearrangements; strained rings

(untitled) - Rubin, M.; Rubina, M.; Gevorgyan, V. (Chem. Rev., 2007)

(untitled) - Marek, I.; Simaan, S.; Masarwa, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Zhu, Z.-B.; Wei, Y.; Shi, M. (Chem. Soc. Rev., 2011)

(untitled) - Miege, F.; Meyer, C.; Cossy, J. (Beilstein J. Org. Chem., 2011)

(untitled) - Vicente, R. (Synthesis, 2016)

(untitled) - Dian, L.; Marek, I. (Chem. Rev., 2018)

Small Ring Compounds in Organic Synthesis VI. Topics in Current Chemistry - Salaün, J. (Cyclopropane Derivatives and their Diverse Biological Activities, 2000)

(untitled) - Donaldson, W. A. (Tetrahedron, 2001)

(untitled) - Talele, T. T. (J. Med. Chem., 2016)

(untitled) - Lautens, M.; Klute, W.; Tam, W. (Chem. Rev., 1996)

(untitled) - Brandi, A.; Goti, A. (Chem. Rev., 1998)

(untitled) - Nakamura, I.; Yamamoto, Y. (Adv. Synth. Catal., 2002)

(untitled) - Brandi, A.; Cicchi, S.; Cordero, F. M.; Goti, A. (Chem. Rev., 2014)

(untitled) - Pellissier, H. (Tetrahedron, 2014)

(untitled) - Audran, G.; Pellissier, H. (Adv. Synth. Catal., 2010)

(untitled) - Köster, R.; Arora, S.; Binger, P. (Angew. Chem., Int. Ed. Engl., 1969)

(untitled) - Vincens, M.; Dumont, C.; Vidal, M. (Tetrahedron, 1981)

(untitled) - Sang, R.; Yang, H.-B.; Shi, M. (Tetrahedron Lett., 2013)

(untitled) - Wiberg, K. B.; Fenoglio, R. A. (J. Am. Chem. Soc., 1968)

(untitled) - Bach, R. D.; Dmitrenko, O. (J. Am. Chem. Soc., 2004)

(untitled) - Shibuya, A.; Okada, M.; Nakamura, Y.; Kibashi, M.; Horikawa, H.; Taguchi, T. (Tetrahedron, 1999)

(untitled) - Weatherhead-Kloster, R. A.; Corey, E. J. (Org. Lett., 2006)

(untitled) - Padwa, A.; Wannamaker, M. W. (Tetrahedron, 1991)

(untitled) - Zohar, E.; Stanger, A.; Marek, I. (Synlett, 2005)

(untitled) - Baumann, A. N.; Music, A.; Karaghiosoff, K.; Didier, D. (Chem. Commun., 2016)

(untitled) - Babin, D.; Pilorge, F.; Delbarre, L. M.; Demoute, J. P. (Tetrahedron, 1995)

(untitled) - Nüske, H.; Bräse, S.; de Meijere, A. (Synlett, 2000)
See for the addition of malonates to π-allyl-palladium complexes derived cyclopropenylmethyl acetates leading to the cyclopropene isomer except in the case of one tertiary acetate.

(untitled) - Yang, Z.; Xie, X.; Fox, J. M. (Angew. Chem., Int. Ed., 2006)

(untitled) - Xie, X.; Yang, Z.; Fox, J. M. (J. Org. Chem., 2010)

(untitled) - Xie, X.; Fox, J. M. (Synthesis, 2013)

(untitled) - Simaan, S.; Masarwa, A.; Bertus, P.; Marek, I. (Angew. Chem., Int. Ed., 2006)

(untitled) - Simaan, S.; Marek, I. (Chem. Commun., 2009)
See for the copper-catalyzed reduction of secondary cyclopropenylcarbinols which has also been reported.

(untitled) - Simaan, S.; Masarwa, A.; Zohar, E.; Stanger, A.; Bertus, P.; Marek, I. (Chem. – Eur. J., 2009)

(untitled) - Masarwa, A.; Stanger, A.; Marek, I. (Angew. Chem., Int. Ed., 2007)

(untitled) - Baird, M. S.; Hussain, H. H.; Nethercott, W. (J. Chem. Soc., Perkin Trans. 1, 1986)

(untitled) - Liron, F.; Knochel, P. (Chem. Commun., 2004)
See for the stereoselective [2,3]-sigmatropic rearrangement of acyclic allylic phosphinites.

(untitled) - Rubina, M.; Woodward, E. W.; Rubin, M. (Org. Lett., 2007)

(untitled) - Muthuramu, K.; Ramamurthy, V. (J. Chem. Soc., Chem. Commun., 1980)

(untitled) - Andrews, S. D.; Day, A. C. (Chem. Commun., 1966)

(untitled) - Maier, G.; Straßer, M. (Tetrahedron Lett., 1966)

(untitled) - Seraya, E.; Slack, E.; Ariafard, A.; Yates, B. F.; Hyland, C. J. T. (Org. Lett., 2010)

(untitled) - Archambeau, A.; Nguyen, D.-V.; Meyer, C.; Cossy, J. (Chem. – Eur. J., 2016)

(untitled) - Obame, G.; Brémond, P.; Pannecouque, C.; Audran, G. (Synthesis, 2013)

(untitled) - Li, K.; Du, W.; Que, N. L. S.; Liu, H.-w. (J. Am. Chem. Soc., 1996)

(untitled) - Zhao, Z.; Liu, H.-w. (J. Org. Chem., 2002)

(untitled) - Kawanaka, Y.; Kobayashi, K.; Kusuda, S.; Tatsumi, T.; Murota, M.; Nishiyama, T.; Hisaichi, K.; Fujii, A.; Hirai, K.; Naka, M.; Komeno, M.; Odagaki, Y.; et al. (Bioorg. Med. Chem., 2003)

(untitled) - Overman, L. E.; Carpenter, N. E. (Org. React., 2005)

(untitled) - Howard, J. K.; Amin, C.; Lainhart, B.; Smith, J. A.; Rimington, J.; Hyland, C. J. T. (J. Org. Chem., 2014)

(untitled) - Nishikawa, T.; Urabe, D.; Tomita, M.; Tsujimoto, T.; Iwabuchi, T.; Isobe, M. (Org. Lett., 2006)

(untitled) - Shinkevich, E.; Deblander, J.; Matthijs, S.; Jacobs, J.; De Kimpe, N.; Tehrani, K. A. (Org. Biomol. Chem., 2011)

(untitled) - Gallego, G.; Ariafard, A.; Tran, K.; Sandoval, D.; Choi, L.; Chen, Y.-H.; Yates, B. F.; Tao, F.-M.; Hyland, C. J. T. (Org. Biomol. Chem., 2011)

(untitled) - Ernouf, G.; Brayer, J.-L.; Folléas, B.; Demoute, J.-P.; Meyer, C.; Cossy, J. (Chem. – Eur. J., 2018)

(untitled) - Roy, S.; Spino, C. (Org. Lett., 2006)

(untitled) - Henrion, S.; Carboni, B.; Cossío, F. P.; Roisnel, T.; Villalgordo, J. M.; Carreaux, F. (J. Org. Chem., 2016)

(untitled) - Schuemacher, A. C.; Hoffmann, R. W. (Synthesis, 2001)

(untitled) - Crabtree, R. H.; Davis, M. W. (J. Org. Chem., 1986)

The Claisen Rearrangement. Methods and Applications - Nubbenmeyer, U.; Hiersemann, M. (Wiley-VCH, 2007)

(untitled) - Gould, T. J.; Balestra, M.; Wittman, M. D.; Gary, J. A.; Rossano, L. T.; Kallmerten, J. (J. Org. Chem., 1987)

(untitled) - Ernouf, G.; Brayer, J.-L.; Folléas, B.; Demoute, J.-P.; Meyer, C.; Cossy, J. (Org. Lett., 2015)

(untitled) - Fattahi, A.; McCarthy, R. E.; Ahmad, M. R.; Kass, S. R. (J. Am. Chem. Soc., 2003)

(untitled) - Chuprakov, S.; Malyshev, D. A.; Trofimov, A.; Gevorgyan, V. (J. Am. Chem. Soc., 2007)

(untitled) - Zrinski, I.; Eckert-Maksić, M. (Synth. Commun., 2003)

(untitled) - Ernouf, G.; Brayer, J.-L.; Folléas, B.; Demoute, J.-P.; Meyer, C.; Cossy, J. (J. Org. Chem., 2017)

(untitled) - Bessard, Y.; Schlosser, M. (Tetrahedron, 1991)

(untitled) - Cheng, Z.-L.; Chen, Q.-Y. (Chin. J. Chem., 2006)

(untitled) - Tian, F.; Kruger, V.; Bautista, O.; Duan, J.-X.; Li, A.-R.; Dolbier, W. R.; Chen, Q.-Y. (Org. Lett., 2000)

(untitled) - Tellam, J. P.; Carbery, D. R. (J. Org. Chem., 2010)

(untitled) - Wang, B.-Y.; Huang, J.-W.; Liu, L.-P.; Shi, M. (Synlett, 2005)

(untitled) - Fu, W.; Huang, X. (Tetrahedron Lett., 2008)